Hybrid Propulsion System to Power Unmanned Aerial Vehicle in Worst Case Scenario - بابه صالح عمر و رحيل عمر عبدالهادي (Journal of Pure & Applied Sciences, 2020)
The present fuel cell systems have demonstrated a high degree of efficiency for automotive applications. Currently the technology is under considerations as potential power source for Unmanned Aerial Vehicles (UAVs). This paper presents an investigation of the fuel cell/battery hybrid propulsion system for PiperCub J3 aircraft in worst case scenario (battery low state of charge) by using the fuzzy logic controller. The hybrid propulsion system consists of a 1.2kW Nexa PEMFC, three 12V batteries, DC/DC converters, and an electrical engine. The fuzzy logic control the output powers of the batteries through the bidirectional DC/DC converter to assisted and maintain the fuel cell operates at optimal point with high efficiency as a main power supply to achieve the desired power for different phases of flight. After completing the test of first flight scenario, the batteries had been operating for a long time.